The Effectiveness of Solution Focused Brief Counseling (SFBC) Based on Creative Art to Reduce Students Social Aggressive Behaviour - Putri, Dhia Adinda; Saputra, Wahyu Nanda Eka; Hartanto, Dody; Nugraha, Ariadi (Universitas Nusantara PGRI Kediri, 2019)
The current study aimed to investigate the effectiveness of SFBC to decrease social agresive behaviour among the students of 12th grade in SMA Muhammadiyah 1 Prambanan. This study was an experiment study and used pre-experimental design employing one group pretest posttest model. The subject of this current study was students of 12th in SMA Muhammdiyah 1 Prambanan. In determining the subject, the researcher used nonprobablility sampling design with purposive sampling. The finding found a significant difference between students' social agresive level before and after they were treated with SFBC based on creative arts.